2009
DOI: 10.1080/01924780903148185
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Used by Communication Partners of Aphasic Speakers

Abstract: This article explores the experiences of communication partners of individuals with aphasia. The social model of aphasia intervention provided a useful framework when addressing the impact of the aphasic person's environment on the success of communication attempts. The communication partners perceived strategies such as maintaining a routine, using multiple communication modalities, and using targeted questions as helpful. Behaviors of the communication partners were considered just as important to establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…CPs of individuals with aphasia [20][21][22] or individuals using alternative and augmentative communication [23]. The educational need was also highlighted by the participants in the current study.…”
Section: Discussionmentioning
confidence: 86%
“…CPs of individuals with aphasia [20][21][22] or individuals using alternative and augmentative communication [23]. The educational need was also highlighted by the participants in the current study.…”
Section: Discussionmentioning
confidence: 86%
“…Significant others are often directly affected by aphasia, 5,6,8,10,11 and they play an important role in rehabilitation. 12,13 Their needs and priorities for rehabilitation should therefore be considered in order to ascertain buy-in and appropriateness of therapeutic intervention to everyday contexts. At the same time, the perspectives of family members/friends and those of the person with aphasia do not always coincide when it comes to aspects concerning the life of the adult with aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…However, when considered in the context of the broader literature, there are several implications for preparing students for interacting with PWA. Previous research has indicated that the way a communication partner interacts with a PWA is as important as the communication abilities of the PWA (Paul & Sanders, 2009;Ross et al, 2006;Simmons-Mackie et al, 2010). Positive attributes of communication partners include active listening, patience, perseverance, and a genuine desire to perceive the intended message; in addition to an appropriate surrounding environment.…”
Section: Implications For Practicementioning
confidence: 99%